The Effect of Digitalization on Economic Development in Bengkalis Regency - Siti Saidah; Shofiyan Hidayat; Nur Jihan Farisha; M Abdul Gapur (ORGANIZE: Journal of Economics, Management and Finance, 2023)
Digitalization in the economic sector certainly cannot be separated from the term digital entrepreneurship, which is often associated with "digital entrepreneurship", "digital economy", "creative industry", and "start-up". According to Dedy Permadi, digital entrepreneurship is an entrepreneurial activity that is supported by the use of technology. This term also refers to the development of innovation and creativity within an organization. Digital entrepreneurship carries responsibility in the form of design and implementation. As well as generating sales value through the production process and developing economic activities. This process is carried out through the use of various technologies and products supported by technology, namely Information and Communication Technology (ICT). Researchers used descriptive qualitative research methods in this study. In this research, various events and events that occurred are described and their nature contains facts, is systematic and accurate. The result shows a using of information technology in the current era, understanding digital economic activity actors is very important, especially for business actors in Bengkalis Regency digitalization has become an intermediary medium that supports the development of more creative and innovative skills in the economic sector, especially the economy in Bengkalis Regency. And also, in order to minimize the dependence of the people of Bengkalis Regency on honorary salaries and reduce APBN expenditure, the Bengkalis Regency government has carried out several activities that benefit MSMEs (Micro, Small and Medium Enterprises).